Digital literacy and language teacher education in contemporary times - Bedran, Patrícia Fabiana (Universidade Estadual Paulista, 2016)
In an attempt to consider and rethink teacher education in a more contemporary perspective, we aim to promote a discussion on the use of information and communication technology (LÉVY, 1998; 1999; 2007) as responsible for (new) literacy practices within education from the reflection and articulation of concepts and perspectives on Digital Literacy (STREET, 1995; BUZATO, 2006; ROJO, 2013) and Sociocultural Education Teacher (VIGOTSKI, 1998; 2010; JOHNSON, 2009; FRIEDRICH, 2012). In order to instigate a reflection on practical experience in the light of this literature, we weave more specific considerations of a qualitative and ethnographic research in an initial teacher education context, which made use of technology aiming at a social, critical and reflective construction of these teachers. The data showed that the success of the activity is not directly related to the use of appropriate technology but to the engagement of the participants in the requested task, which implies a new way of thinking and acting.